2015
DOI: 10.3174/ajnr.a4564
|View full text |Cite
|
Sign up to set email alerts
|

3D T2 MR Imaging–Based Measurements of the Posterior Cervical Thecal Sac in Flexion and Extension for Cervical Puncture

Abstract: BACKGROUND AND PURPOSE:The current standard technique for cervical puncture involves prone positioning with neck extension. The purpose of this study was to compare measurements of the posterior cervical thecal sac during neck flexion and extension in supine and prone positions by using high-resolution MR imaging to help determine the optimal positioning for cervical puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To our knowledge, no one has reported normal CXA values using 3D MRI during neck flexion and extension within the scanner, although a similar approach has been used to measure the posterior cervical subarachnoid space accurately. 23…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no one has reported normal CXA values using 3D MRI during neck flexion and extension within the scanner, although a similar approach has been used to measure the posterior cervical subarachnoid space accurately. 23…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, it is used for the detection of cerebellar tonsillar movement in Chiari I malformation, evaluation of arachnoid granulations, evaluation of third ventriculostomy patency, determination of etiology of hydrocephalus, and localization of spinal dural arteriovenous fistulas (5,6,(14)(15)(16). Besides, there are studies showing normal anatomy at the cervical spinal level both statically and dynamically (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Our absolute measurements of the width of the SAS are nearly identical to an MRI study, which reported a widening of the posterior SAS on average from 0.4 cm in neutral position to 0.5 cm in extension. 8 The head position -SAS width index seems to be a parameter sensitive to detect this phenomenon independent of variations of the width of the spinal canal and the SAS between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…That spinal level is of special interest for radiologists performing a myelography at C1-C2. We compared the SAS in different head positions because previous radiological and magnetic resonance imaging (MRI) studies have shown that the posterior cerebrospinal fluid space enlarges with the head in extension position, which can facilitate the dural puncture 8,9 …”
mentioning
confidence: 99%